On the microscopic structure of liquid hydrogens - Zoppi, M.; Celli, M.; Bafile, U.; Guarini, E.; Neumann, M. (Condensed Matter Physics, 2001)
Among the quantum liquids, the hydrogens cover an interesting position
between liquid helium, where quantum exchange gives rise to the macroscopic
phenomenon of superfluidity, and neon, where quantum effects are
relatively small, so that its features can be evaluated by perturbation methods
with reference to a classical system. Nonetheless, the experimental
access to the microscopic structure of the hydrogens is not an easy task
both because of their intra-molecular structure and the small molecular
mass that is comparable with that of the neutron probe. In this paper we
discuss the state of the art and summarise the available experimental information
on the microscopic structure of the hydrogens. The experimental
data for the two systems are compared among them and with the results
of quantum Path Integral Monte Carlo simulations. It is found that similar
quantities, measured in corresponding thermodynamic points, are rather
different for the two systems due to the different weight of quantum effects.
Moreover, the comparison with the simulation results shows that, for deuterium,
there is a substantial agreement, both at the level of the structure
factor and its thermodynamic derivatives. The agreement is less satisfactory
for liquid hydrogen. Серед квантових рідин водень займає цікаве місце між рідким гелієм, для якого квантовий обмін приводить до макроскопічного явища надплинності, і неоном, для якого квантові ефекти відносно малі,
так що його властивості можуть бути оцінені методами збурень відносно класичної системи. Тим не менше, експериментальний підхід
до мікроскопічної структури водню не є легким завданням як через
його внутрішню молекулярну структуру, так і через малу молекулярну масу, що співмірна з масою нейтронів. У цій статті ми обговорюємо стан справ і підсумовуємо наявну експериментальну інформацію
про мікроскопічну структуру водню. Експериментальні дані для двох
систем порівнюються між собою і з результатами розрахунку інтегралів за траєкторіями методом Монте Карло. Знайдено, що подібні
величини, виміряні у відповідних термодинамічних точках, є швидше
відмінні для двох систем завдяки різним вкладам квантових ефектів.
Більше того, порівняння з результатами моделювання показують, що
для дейтерію спостерігаються суттєві узгодження як на рівні структурного фактора, так і його термодинамічних похідних. Узгодження є
менш задовільним для рідкого водню.